Pelatihan Pembuatan Video Pembelajaran Dengan Aplikasi Bandicam dan Screencast O-Matic - Ofirenty Elyada Nubatonis (Jurnal Nasional Pengabdian Masyarakat, 2021)
The problem faced by teachers in East Nusa Tenggara is the limited use of technology in producing instructional media or digital audio-visual teaching materials. The impact of this limitation was most felt during the Covid-19 pandemic, online learning did not work effectively. Finally, the Network learning process is carried out which happens to the extent that the teacher sends the assignment and the students do the given assignment and then sent it back via the messenger application. When the teacher sends teaching materials in the form of instructional videos to explain certain concepts, most of the videos are taken from the internet and are not written by themselves. Therefore, it is necessary to hold training in making learning videos using applications that are easy to master, do not require money, and simply use a laptop. In this activity, teachers are provided with the knowledge and practice of making instructional videos using the Bandicam and Screencast O-Matic applications. The form of this activity is online training. The methods used are seminars, lectures, discussions, and mentoring. The results of this activity were 1) increased teacher knowledge about the use of the Bandicam and Screencast O-Matic applications in making instructional videos, 2) teachers were able to develop instructional videos using Bandicam and Screencast O-Matic